2009
DOI: 10.1103/physreve.80.021110
|View full text |Cite
|
Sign up to set email alerts
|

Complexity and synchronization

Abstract: We study a fully connected network ͑cluster͒ of interacting two-state units as a model of cooperative decision making. Each unit in isolation generates a Poisson process with rate g. We show that when the number of nodes is finite, the decision-making process becomes intermittent. The decision-time distribution density is characterized by inverse power-law behavior with index = 1.5 and is exponentially truncated. We find that the condition of perfect consensus is recovered by means of a fat tail that becomes m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
108
0
1

Year Published

2011
2011
2014
2014

Publication Types

Select...
3
2
2

Relationship

4
3

Authors

Journals

citations
Cited by 67 publications
(111 citation statements)
references
References 34 publications
2
108
0
1
Order By: Relevance
“…(1) with μ = 1.5. We note that when K > 1, the DM model has two equilibrium states corresponding to the bottoms of a double-well potential [26]. At criticality the barrier disappears, resulting in the potential of Eq.…”
Section: Renewal Non-poisson Fluctuationsmentioning
confidence: 99%
“…(1) with μ = 1.5. We note that when K > 1, the DM model has two equilibrium states corresponding to the bottoms of a double-well potential [26]. At criticality the barrier disappears, resulting in the potential of Eq.…”
Section: Renewal Non-poisson Fluctuationsmentioning
confidence: 99%
“…The foundation of these papers is sociological and similar to that of the economical model illustrated in the work of Sornette [15]. Thus, the authors [18,19] did not discuss the connection of the DMM with the Ising model and adopted the nonrealistic but often made assumption of all-to-all coupling among the network's units, thereby confining the emergence of an inverse power law, namely, of temporal complexity, to the same time scale as that of the units in isolation.…”
Section: Introductionmentioning
confidence: 99%
“…The thermodynamical condition M = L = ∞ was discussed extensively by authors of [18,19], who showed that under those conditions the ratios…”
Section: Detailed Description Of the Modelmentioning
confidence: 99%
See 2 more Smart Citations